2022
DOI: 10.3390/ani12030406
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Yields and Meat Composition of Male and Female Italian Slow-Growing Chicken Breeds: Bianca di Saluzzo and Bionda Piemontese

Abstract: The slaughter performance and meat quality of two native Italian chicken breeds, Bionda Piemontese (BP, n = 64) and Bianca di Saluzzo (BS, n = 64), were investigated. Two-way ANOVA, considering breed, sex, and their interaction, was used to compare the properties of birds slaughtered at 5, 6, 7, and 8 months of age. Subsequently, data were analyzed using one-way ANOVA and the Duncan test to evaluate the differences between slaughter ages. The BP breed produced a better carcass yield than BS at 5, 7, and 8 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
9
16
0
Order By: Relevance
“…Compared with female, male exhibited higher breast muscle crude protein contents than thigh meat, but not the crufe fat content. A recent study reported that two Italian slow-growing chicken breeds also exhibited the same results [ 7 ]. Another study reported that the higher crude fat contents in female meat contributed to estrogen production, promoting lipid synthesis and deposition during the sexual maturity of birds [ 19 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared with female, male exhibited higher breast muscle crude protein contents than thigh meat, but not the crufe fat content. A recent study reported that two Italian slow-growing chicken breeds also exhibited the same results [ 7 ]. Another study reported that the higher crude fat contents in female meat contributed to estrogen production, promoting lipid synthesis and deposition during the sexual maturity of birds [ 19 ].…”
Section: Discussionmentioning
confidence: 86%
“…The ultimate goal is to provide high levels of growth performance and quality of their meat. The development and composition of breast and thigh muscles, as the main meat-producing parts of chickens, are affected by breed [ 6 ], sex [ 7 ], nutrition [ 8 ], intestinal microbial species [ 9 ], and rearing systems [ 10 ]. Chicken is a favorite food product for healthy eating because it contains higher levels of protein as well as lower fat content than other meats.…”
Section: Introductionmentioning
confidence: 99%
“…Meat moisture plays a fundamental role in meat quality, being responsible for its perceived juiciness [ 50 ]. Moisture content can be affected by age [ 51 ], and a higher content indicates a lower physiological maturity state.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current findings, Tangnet al ( 17 ) found that the indigenous chicken types had equal or even lower PUFA contents in the intramuscular lipids. In a more recent research, Bongiorno et al ( 36 ) also revealed similar PUFA contents in the breast and thigh muscles of indigenous Italian chicken breeds. Given that poultry meat is one of the main sources of PUFA in developed economies ( 30 ), spent laying hens might be used as a low-cost, moderate-quality meat source.…”
Section: Discussionmentioning
confidence: 71%